Interaksi Sosial di Era Digital: Dampak Media Sosial Terhadap Perubahan Budaya - Rut Kristina Hutabarat (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
In the digital era, social interactions have undergone significant changes. The influence of technology has changed the way people communicate and interact with each other. Social interactions are no longer limited by time and space. People can connect and interact from anywhere and at any time. Social interaction in the digital era has the potential to improve the quality of human life. However, it is important to use technology wisely so that it does not cause negative impacts. The aim of this research is to determine the basic needs and aspirations of humans that arise amidst technological developments. This journal is presented using a descriptive method accompanied by a literature review as a comparative study of similar publications in previous relevant scientific papers.